Association between gastroesophageal reflux disease and stroke: a bidirectional Mendelian randomization study - Meng, Decheng; Zhang, Xin; Yu, Wenfei; Yin, Guoliang; Chen, Suwen; Liu, Hongshuai; Wang, Linya; Zhang, Fengxia (Frontiers in Neurology, 2024)
Objective Some previous studies have suggested a potential link between stroke and gastroesophageal reflux disease (GERD). We used a two-sample bidirectional Mendelian randomization (MR) method to explore the causal relationship between stroke and GERD. Design Summary-level data derived from the published genome-wide association studies (GWAS) were employed for analyses. Single-nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for stroke (n = 446,696) and its common subtypes ischemic stroke (IS) (n = 440,328), large vessel stroke (LVS) (n = 410,484), small vessel stroke (SVS) (n = 198,048), and cardioembolic stroke (CES) (n = 413,304) were obtained from the MEGASTROKE consortium. The data on intracerebral hemorrhage (ICH) (n = 721,135) come from the UK Biobank. Instrumental variables (IVs) for lacunar stroke (LS) (n = 474,348) and GERD (n = 602,604) were screened from publicly available genetic summary data. The inverse variance weighted (IVW) method was used as the main MR method. Pleiotropy was detected by the MR-Egger intercept test, MR pleiotropy residual sum and outlier, and leave-one-out analysis. Cochran Q statistics were used as supplements to detect pleiotropy. Results We found that GERD can causally increase the risk of stroke [IVW odds ratio (OR): 1.22, 95% confidence interval (CI): 1.13–1.32, p = 1.16 × 10−6] and its common subtypes IS (OR: 1.19, 95% CI: 1.10–1.30, p = 3.22 × 10−5), LVS (OR: 1.49, 95% CI: 1.21–1.84, p = 1.47 × 10−4), and LS (OR: 1.20, 95% CI: 1.001–1.44, p = 0.048). Several important risk factors for stroke have also been implicated in the above causal relationship, including type 2 diabetes, sleep apnea syndrome, high body mass index, high waist-to-hip ratio, and elevated serum triglyceride levels. In reverse MR analysis, we found that overall stroke (OR: 1.09, 95% CI: 1.004–1.19, p = 0.039) and IS (OR: 1.10, 95% CI: 1.03–1.17, p = 0.007) have the causal potential to enhance GERD risk. Conclusion This MR study provides evidence supporting a causal relationship between GERD and stroke and some of its common subtypes. We need to further explore the interconnected mechanisms between these two common diseases to better prevent and treat them.